A boundary analysis of ICT firms on Thailand Stock Market: a maximum entropy bootstrap approach and highest density regions (HDR) approach. (6th September 2013) - Chaiboonsri, Chukiat; Chaitip, Prasert
This common aim provides a general framework for specifying, estimating, and testing time series econometric models using maximum entropy bootstrap (MEB) to test with data in time series from Stock Market of Thailand. The MEB is quantitatively reviewed for the first time to investigate the relation between SET Index of Thailand and stock prices of ICT firms, True, DTAC, and AIS. An influence significant relationship covering three companies listed in the technology industry group, information and communication technology (ICT) Sector during period of 2008–2012 (daily data) was investigated. The study indicated the identified significant statistical boundaries in ICT's Stock Market of Thailand (SET). An exact boundary of an influence significant relationship showed that believed maximum entropy bootstrap with powerful tool than conventional statistics. An estimation result of the experiment can significantly improve the prediction accuracy of simple regression analysis method.